“First responder” bike ambulance service in India: An innovative concept by the provider end - Mahendra M Reddy; Bijaya Nanda Naik; Kalaiselvi Selvaraj; Srikanta Kanungo; Manisha Verma; Anuvarshini Ramalingam (CHRISMED Journal of Health and Research, 2021)
Most of the deaths due to road traffic injuries occur outside the hospital. However, the trauma care system in India is still in the nascent stage to provide emergency prehospital health-care services. The emergency prehospital trauma health-care services are mostly limited to the urban areas in India. The heavy traffic in urban areas, adverse topography, poor health infrastructure, and unavailability of skilled human resources in the rural areas limit the provision of prehospital trauma care services in India by using traditional car ambulance. The bike ambulance service and the first responder seems to complement each other to provide prehospital emergency trauma care services in the every corner of India negotiating the constraints faced by car ambulance services. The bike ambulance service has been started in few cities across few states/union territories in India, but it has a long way to go. Inadequate public funding, lack of guidelines, and skilled workforce form the bottle neck in rolling out of bike ambulance services across India. The government can take the opportunity of the services of vast network of nongovernmental organizations (NGO), self-help groups, youth clubs, and other social organizations to make this initiative an exemplary solution for providing optimum prehospital emergency trauma care services.